Konsep Childfree Perspektif Pendidikan Keluarga Dalam Islam - Wathoni, Kharisul Wathoni; Hijriyani, Yuli Salis; Azizah, Alda Ismi (Institut Agama Islam Negeri Ponorogo, 2023)
Since the 19th century, interactions between humans have begun to be carried out in new ways that are not bound by distance, which causes no barriers between various parts of the world. All phenomena that occur can be seen clearly in a relatively short time. Various cultures and traditions began to mingle and lose their identity. One of the things that has become a hot topic of discussion from the western world in recent months is childfree, namely the decision of a married couple not to have children with several factors being the reason. In the Western world, childfree is not a complicated thing to be debated. However, what about the Eastern world, especially Indonesia with the thick rules of each religion. Moreover, Islam adheres to the holy book al-Qur'an, in which it is narrated that Prophet Ibrahim a.s. and the Prophet Zakaria a.s pleaded with God to be given offspring from the pious group, as stated in the QS. As-Saffat verse 100 and QS. Maryam verses 4 to 5. From an Islamic perspective, children are something that is highly coveted and fought for in marriage. A child seems to be a glory for his parents, not only in this world but also into the hereafter. Hasan as-Sayyid Hamid Khitob in his book Maqasi>d an-Nika>h wa Atharuha> explains that among the main purposes of marriage are expecting children, multiplying the descendants of the people of the Prophet Muhammad SAW., guarding the genitals, and maintaining lineage. But what if it is related to the childfree phenomenon which is starting to be followed by many people in Indonesia who are even Muslim, where they actually do not want to bring children into their marriage.",